2018
DOI: 10.1159/000489290
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Arterial Lesions Are Associated with Higher Blood Pressure, Reduced Renal Function and Poorer Renal Outcomes in Patients with IgA Nephropathy

Abstract: Background/Aims: Arterial fibrotic intimal thickening and arteriolar hyaline are considered common pathological features in immunoglobulin A nephropathy (IgAN), whereas little is known about the acute pathological manifestations of endothelial cell injury. The aim of this study was to investigate characteristics of intrarenal arterial lesions and to estimate their prognostic values in patients with IgAN. The primary renal endpoint was a 50% reduction in estimated glomerular filtration rate (eGFR) or end-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…This higher prevalence may be explained-at least in part-by the fact that El Karoui et al re-examined the renal biopsies with the specific aim of identifying microangiopathic lesions, as well as the fact that patients were selected from an active hypertensive clinic. Although the patients in our cohort did not come from a hypertension clinic, we re-examined at least four different biopsy sections from each patient and found that 23% of biopsies with IgA nephrtopathy had microangiopathy with or without thrombosis, which is higher than we had expected based on other studies [4,[29][30][31]. Thus, our findings indicate that microangiopathy may be underdiagnosed in clinical practice, which is an important point given our finding that microangiopathy is clinically relevant-specifically, we found that patients with microangiopathy had a higher prevalence of hypertension, a higher number of chronic lesions, and poorer renal outcome compared to patients without microangiopathy.…”
Section: Discussionmentioning
confidence: 71%
“…This higher prevalence may be explained-at least in part-by the fact that El Karoui et al re-examined the renal biopsies with the specific aim of identifying microangiopathic lesions, as well as the fact that patients were selected from an active hypertensive clinic. Although the patients in our cohort did not come from a hypertension clinic, we re-examined at least four different biopsy sections from each patient and found that 23% of biopsies with IgA nephrtopathy had microangiopathy with or without thrombosis, which is higher than we had expected based on other studies [4,[29][30][31]. Thus, our findings indicate that microangiopathy may be underdiagnosed in clinical practice, which is an important point given our finding that microangiopathy is clinically relevant-specifically, we found that patients with microangiopathy had a higher prevalence of hypertension, a higher number of chronic lesions, and poorer renal outcome compared to patients without microangiopathy.…”
Section: Discussionmentioning
confidence: 71%
“…Kaneko et al reported that AH was associated with renal prognosis on univariate and multivariate analyses, considering other MEST‐C scores, but not with clinical findings or RASI [ 5 ]. Zhang et al reported that AAS was associated with renal prognosis on univariate analysis, and that RASI prevented ESRD in patients with vascular lesions, including AAS and acute arterial lesions, such as arteriolar endothelial swelling, inflammatory cell infiltration, and thrombosis [ 18 ]. These previous reports support the hypothesis and results of this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…17,28 However, vascular lesions, such as arterial intima fibrosis, arteriolar hyalinosis, and microangiopathy, have recently been shown to be associated with worse outcome. 18,23,25 In particular, microangiopathic lesions have been proposed to be incorporated in the classification. 22,23 Interestingly, C4d has been shown to be a reliable general marker for thrombotic microangiopathy in various kidney diseases, 24 including IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…15 The vascular compartment is neglected by the Oxford pathologic classification because its significance in predicting kidney outcomes is uncertain. [16][17][18][19] Nevertheless, the impact of risk factors for vascular disease on the progression of IgAN has been shown in numerous studies. 5,[19][20][21] Additionally, microangiopathic lesions in IgAN biopsy specimens have been associated with worse prognosis.…”
Section: Arteriolar C4d In Iga Nephropathy: a Cohort Studymentioning
confidence: 99%